If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = 19 + -2b Solving 11 = 19 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. 11 + 2b = 19 + -2b + 2b Combine like terms: -2b + 2b = 0 11 + 2b = 19 + 0 11 + 2b = 19 Add '-11' to each side of the equation. 11 + -11 + 2b = 19 + -11 Combine like terms: 11 + -11 = 0 0 + 2b = 19 + -11 2b = 19 + -11 Combine like terms: 19 + -11 = 8 2b = 8 Divide each side by '2'. b = 4 Simplifying b = 4
| (2x-80)=x | | -2x-28=67-7x | | (5a-3)(5a-3)= | | 2x/x-9-x/2(x-9)= | | 3(2x-5)-(x+3)=(2x+1)+4 | | 7=10-3u | | 5a-2=3a+4 | | 2(x-4)+12=x-4(6+2x)+9x | | 12×-1/3 | | 13=10 | | 3log(2)x=28 | | -53/4-31/2= | | 4x-40=13-6x+3 | | 2y-10x=10 | | 3.50x=10.50 | | 3x^2+10=100 | | 2x+7=15+4x | | 2x+12+9=x+3 | | 6x+5+9x-10+80+90=360 | | X+6=-8x+5 | | (x^2+0.8)(x^2+0.8)= | | 3x-29=17-5x | | 18=9+3h | | 7tanx+2=9 | | 3y+6-2=8-2y | | 7/3*8/6 | | -4/7y16 | | 12=15-3p | | 2(x-4)+12=x-4(6+2x)+9 | | 42r^2-35r=0 | | -5+1y=-8x | | 15=2v+3 |